Influence of Environmental Stress on Enumeration of Indicator Bacteria from Natural Waters - Bissonnette, G. K. (1975)
The problems associated with recovery of pure cultures of Escherichia coli and Streptococcus faecalis from stream environments were examined utilizing membrane filter chambers. It was observed that upon exposure to the aquatic environment a significant proportion of cells lost their ability to produce colonies on a selective medium, yet retained this capability on a nutritionally rich, nonselective medium. Discrepancies in colony-forming units between nonselective and selective media indicated that a substantial portion of bacterial cells may become physiologically injured due to the environmental stress imposed by the aquatic environment. The extent of injury was observed to vary considerably among the eight different stream environments, since the amount of injury was not uniform for all types of water environments examined. It was observed that the injury acquired by a population of E. coli, during exposure to the aquatic environment, could be rapidly repaired in a nutritionally rich, nonselective medium. As the injured population of cells was exposed to the rich, nonselective broth, increasing proportions of cells were able to repair themselves such that they became insensitive to inhibitory agents in selective media.